EVALUASI PROGRAM KKG GUGUS MUWARDI KECAMATAN TINGKIR KOTA SALATIGA TAHUN 2017/2018 - Agus Hadhiansyah (Universitas Negeri Malang, 2020)
Abstract: The purpose of this study was to evaluate the context, input, process, and product components of the Muwardi Cluster KKG program, Tingkir District, Salatiga City. This study is evaluation research with a qualitative description approach using the CIPP model. Data collection techniques through interviews, observation, and study of documents. Data analyzed through: data collection, data reduction, data presentation, and conclusions. Data validation uses the triangulation of sources and techniques. The results of the study show: (1) Context, the Muwardi Cluster KKG program is a need of teachers as a place for self-development, besides that it is a coaching program that is fully supported by the Salatiga City Education Office as an effort to develop teacher competencies and help solve problems that occur during the activity process teaching and learning, (2) Inputs, answering program needs following government standards and technical guidelines. Seen from the planning, mechanism, human resources, and financing of the KKG program, almost all of them are sufficient. The aspects that are not yet adequate and support the implementation of the KKG program are in terms of infrastructure. (3) Process, the Muwardi Cluster KKG program in terms of the process has been carried out following the planning. Only it has constraints in the form of limited funds, member enthusiasm, inadequate infrastructure, and has no public relations and development fields. (4) Product, Muwardi Cluster KKG program is following the objectives and targets so that it has an impact on improving the quality of education in the Muwardi Cluster area. Muwardi Cluster KKG program can be continued in the coming year with improvements in several aspects. Abstrak: Tujuan penelitian ini adalah untuk melakukan evaluasi terhadap komponen konteks, input, proses, produk dari program KKG Gugus Muwardi Kecamatan Tingkir Kota Salatiga. Penelitian ini adalah penelitian evaluasi dengan pendekatan deskripsi kualitatif menggunakan model CIPP. Teknik pengumpulan data melalui wawancara, observasi dan studi dokumen. Data dianalisis melalui: koleksi data, reduksi data, penyajian data, dan kesimpulan. Validatas data menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan: (1) Konteks, program KKG Gugus Muwardi merupakan kebutuhan dari para guru sebagai wadah pengembangan diri, disamping itu merupakan program pembinaan yang didukung penuh oleh Dinas Pendidikan Kota salatiga sebagai upaya pengembangan kompetensi guru serta membantu memecahkan masalah yang terjadi selama proses kegiatan belajar mengajar, (2) Input, menjawab kebutuhan program sesuai dengan standar dan juknis dari pemerintah. Dilihat dari perencanaan, mekanisme, SDM, serta pembiayaan program KKG hampir semua telah memadai. Adapun aspek yang belum memadai serta mendukung pelaksanaan program KKG adalah dari segi sarana prasarana. (3) Proses, program KKG Gugus Muwardi dari segi process telah dilaksanakan sesuai dengan perencanaan hanya saja memeiliki kendala berupa keterbatasan dana, antusiasme anggota, sarana prasarana tidak memadai, serta tidak memiliki bidang humas dan pengembangan. (4) Produk, program KKG Gugus Muwardi telah sesuai dengan tujuan dan target sehingga berdampak pada peningkatan kualitas pendidikan di wilayah Gugus Muwardi. Sehingga program KKG Gugus Muwardi dapat dilanjutkan pada tahun berikutnya dengan perbaikan dibeberapa aspek.